Eugenia paranapanemensis (Myrtaceae), the Pitanga-amarela, and a Key to Eugenia sect. Eugenia Species from São Paulo State, Brazil - Valdemarin, Karinne S.; Camargo, Paulo H. S. A. [UNESP]; Moreno, Daniele Janina; Souza, Vinicius Castro; Lucas, Eve; Mazine, Fiorella F. (My University, 2022)
A new species popularly known as pitanga-amarela, Eugenia paranapanemensis, from Seasonal Forest vegetation in the Atlantic Forest of São Paulo state is described. Our analysis, based on morphological data, shows that this species belongs to Eugenia sect. Eugenia. Among the species in the Eugenia sect. Eugenia clade, E. paranapanemensis can be recognized by its height of about 25 m, flowers with a smooth and pubescent hypanthium, brownish to ochraceous trichomes, and fruits that are yellow when ripe, with up to six seeds.
Keywords: Atlantic Forest; conservation; ecology; Myrteae; new species; Penelope; Ramphastos; Seasonal Forest; Tangara